KEARIFAN LOKAL CABLAKA SEBAGAI UPAYA PEMBERANTASAN KORUPSI SECARA NON PENAL - Kartika Winkar Setya (Economics, Social, and Humanities Journal (Esochum), 2022)
Eradication of criminal acts of corruption is still being promoted at the central and regional levels, both penal and non-penal. In relation to the eradication of corruption in a non-penal manner, there is local wisdom in the Banyumas area and its surroundings which has turned out to be one of the efforts to fight corruption, namely the character of Cablaka. Cablaka's character as a noble value that lives, grows and develops among the people of Banyumas and its surroundings prioritizes being honest, open and candid. This study aims to find and create a concept against corruption based on local wisdom in the form of cablaka characters. The research method used was a normative juridical method with a conceptual approach. The specification of this research was to examine and analyze the relationship between the character of cablaka and the eradication of corruption in a non-penal manner. Sources of data used were in the form of secondary data to obtain objective research results from the research carried out which includes primary legal materials, secondary legal materials and tertiary legal materials obtained through the study of documents and related library materials. The data analysis method used was a qualitative data analysis method presented in the form of narrative text. Based on the results of the research conducted, it shows that through the cultivation of the Cablaka character from an early age, it can form an honest personal character so that it is relevant to fight and counteract the corrupt nature that gives birth to corruption.